2003
DOI: 10.1074/jbc.m301905200
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Interaction of PSD-95 with 5-HT2A Serotonin Receptors Regulates Receptor Trafficking and Signal Transduction

Abstract: (1) but not all hallucinogens (2, 3) and is the target of a number of commonly prescribed therapeutic agents including atypical antipsychotics, antidepressants, and anxiolytics (4, 5). As with other G protein-coupled receptors (GPCRs) (6 -8), elucidating the regulatory mechanisms for 5-HT 2A receptor signaling and trafficking provides important insights into the therapeutic mechanisms of drugs that target the 5-HT 2A receptor and has implications for the rational design of novel medications (5, 6).The 5-HT 2A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(145 citation statements)
references
References 49 publications
(46 reference statements)
7
138
0
Order By: Relevance
“…1G-I), confirming that this major synaptic protein of the excitatory post-synaptic density was appropriately sorted to the plasma membrane of cortical pyramidal neurons in culture. Furthermore, PSD-95 is known to associate directly with NMDA ionotropic glutamate receptors (NMDA-R) and indirectly with AMPA ionotropic glutamate receptors (AMPA-R) via stargazin (Kornau et al, 1995;Chen et al, 2000;El-Husseini et al, 2000;Chetkovich et al, 2002;Choi et al, 2002;Schnell et al, 2002), and has been shown to directly interact with the 5-HT 2A receptor (Xia et al, 2003). As expected, PSD-95 in cultured neurons co-localized with NMDA receptors (data not shown) and 5-HT 2A receptors (Fig.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…1G-I), confirming that this major synaptic protein of the excitatory post-synaptic density was appropriately sorted to the plasma membrane of cortical pyramidal neurons in culture. Furthermore, PSD-95 is known to associate directly with NMDA ionotropic glutamate receptors (NMDA-R) and indirectly with AMPA ionotropic glutamate receptors (AMPA-R) via stargazin (Kornau et al, 1995;Chen et al, 2000;El-Husseini et al, 2000;Chetkovich et al, 2002;Choi et al, 2002;Schnell et al, 2002), and has been shown to directly interact with the 5-HT 2A receptor (Xia et al, 2003). As expected, PSD-95 in cultured neurons co-localized with NMDA receptors (data not shown) and 5-HT 2A receptors (Fig.…”
Section: Resultssupporting
confidence: 65%
“…We have recently obtained convincing evidence that PSD-95, a prototypic PDZ domain-containing protein and a key component of the excitatory post-synaptic density, directly associates with the PDZ-binding domain of the 5-HT 2A receptor and regulates the signaling and subcellular distribution of 5-HT 2A receptors (Xia et al, 2003). Interestingly, whereas the PDZ-binding domain of the mGluR7 receptor (⌽ -X-⌽, where ⌽ is a hydrophobic residue) is recognized by class II PDZ domains, that of the 5-HT 2A receptor (S/T-X-V/I) is recognized by class I PDZ domains.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the reduction in 5-HT 2A receptor signal was retained after many cell passages, a genetic alteration is likely, either in the receptor itself or key regulatory factors, such as multidomain scaffolding proteins. For example, recent evidence suggests that the 5-HT 2A receptor (Xia et al, 2003) and its close relative, the 5-HT 2C receptor (Parker et al, 2003), are regulated by interaction with a multifunctional PDZ domain protein. In addition, genetic studies have suggested that polymorphisms of the 5-HT 2A receptor are associated with mood disorders, but the results have been mixed (Zhang et al, 1997;Spurlock et al, 1998;Turecki et al, 1999;Du et al, 1999;Hrdina and Du, 2001;Crawford et al, 2000;Arias et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown an interaction of 5-HT 2A receptors with postsynaptic density protein 95 (PSD-95), a PSD-95͞discs large͞ZO-1 (PDZ) domain-containing scaffolding protein that interacts with the extreme C-terminal tail of the 5-HT 2A receptor via a canonical type 1 PDZ ligand (18). In addition, a number of other GPCRs have previously been shown to interact with PDZ domain-containing scaffolding proteins (see ref.…”
Section: Discussionmentioning
confidence: 99%